Is neck posture subgroup in late adolescence a risk factor for persistent neck pain in young adults? a prospective study - Richards, Karen; Beales, Darren; Smith, A.L.; O'sullivan, P.B.; Straker, Leon (OXFORD UNIV PRESS INC, 2021)
Objective: The purpose of this study was to determine whether sagittal neck sitting posture subgroup membership in late adolescence was a risk factor for persistent neck pain (PNP) in young adults. Methods: There were 686 participants enrolled in the Raine Study at the 17- and 22-year follow-ups. At 17 years of age, posture was measured by photographs, and 4 subgroups of sitting neck posture were determined by cluster analysis. Height and weight were measured, and exercise frequency, depression, and PNP were assessed by questionnaire. At 22 years of age, participants answered questions about neck pain and occupation type. Logistic regression examined if neck posture subgroups at 17 years of age were a risk factor for PNP at 22 years of age, taking into account other factors. Results: Female sex (odds ratio [OR] = 1.75, 95% CI = 1.16-2.65) and PNP at 17 years of age (OR = 3.78, 95% CI = 2.57-5.57) were associated with PNP at 22 years of age. In females, neck posture subgroup at 17 years of age was a risk factor for PNP at 22 years of age. Compared with the upright subgroup, both the slumped thorax/forward head subgroup groups and the intermediate subgroup had decreased odds for PNP at 22 years of age (OR = 0.24, 95% CI = 0.08-0.76; OR = 0.38, 95% CI = 0.15-0.99, respectively). No association was found in males. Conclusion: After taking into account PNP at 17 years, sitting neck posture at 17 was not a risk factor for PNP at 22 years of age in males, whereas in females, more relaxed postures (slumped thorax/forward head and Intermediate postures) were protective of neck pain compared with upright posture. Impact: Females in late adolescence who sat in slumped thorax/forward head or intermediate posture rather than upright sitting posture had a lower risk of PNP as a young adult. The practice of generic public health messages to sit up straight to prevent neck pain needs rethinking.